Understanding the Nature of Sentence Complexity in English (El-Wahat Journal for Research and Studies, 2023)
Abstract:The present paper is an attempt to shed light on the notion of sentence complexity in the English language. It introduces a clear definition of the notion of sentence. It also provides a detailed explanation of the relationships between clauses, linking and subordination. Furthermore, it deals with the types of interdependency which are paratactic and hypotactic relationships in addition to the logico-semantic relationships between clauses as expansion and projection.Keywords: sentence complexity, paratactic relationship, hypotactic relationship, expansion, projection.ملخص: يقدم هذا البحث  نظرة عامة عن الجملة في اللغة الانجليزية و تعقيداتها من خلال تقديم تعريف واضح لمصطلح الجملة مع ذكر أنواعها  المختلفة و والتي هي كالتالي، الجملة البسيطة و الجملة المعقدة والجملة المركبة .كما تقدم هذه الدراسة شرحاً مفصلا ًللعلاقات بين العبارات والتي هي الربط و التبعية .كما تذكر الدراسة أنواع الاعتماد المتبادل بين العبارات، والمتمثلة في علاقات التجاور والتلامس و نضيف إلى ذلك علاقات المنطق الدلالي بين العبارات، والمتمثلة في علاقات التوسع وعلاقات الإسقاط.كلمات دالة:  تعقيد الجملة ،علاقات التجاور، علاقات التلامس ،التوسيع ، الاسقاط.